Formation of Research Vision in Schoolchildren Using Digital Mediation Tools according to Cultural-Historical Psychology. Part 1 - E.N. Pavlovsky; T.A. Sidorova; S.A. Smirnov; B.N. Tuchinov (Культурно-историческая психология)
The article sets a task to create and implement models of schoolchildren's development, which are based on the basic ideas of the cultural-historical approach proposed by L.S.Vygotsky's scientific school. The authors of the article believe that such models can help to overcome the limitations of explanatory models, this hypothesis is based on stimulus-reactive algorithmic strategies that negatively affect human development. Using the material of the project "Schoolchildren as Scientific Volunteers", the authors of the article show how this mediation model can be arranged usштп digital tools and a system with elements of artificial intelligence. The project sets the task of forming a research vision (a new functional organ) in schoolchildren with the help of digital mediating tools. Using a cultural-historical approach to AI as a means of developing thinking and research skills while working with information, we propose to consider ethical AI frames as part of an educational environment that promotes the adaptation of risky technologies.. Critical analysis of risk-generating technologies has been developed in bioethics. As ethical guidelines, we use the principles of precaution and proactive response. This article is the first part, which describes the preparatory phase of the study. The second part will show how the project proceeded, what the first results were and what difficulties were met during the implementation of the tasks.